Exogenous testosterone in a non-social provocation paradigm potentiates anger but not behavioral aggression - Panagiotidis, Despina; Schneider, Isabella (European neuropsychopharmacology, 2017)
Animal studies suggest a causal link between testosterone and aggression. However, in human research the exact role of this hormone is still unclear, having been linked to dominance and approach behavior rather than to aggression per se. In a social context, the induction of aggression might be confounded with dominance or status changes, which potentially influence the association between aggression and testosterone. The objective of the current study was to investigate the influence of testosterone on non-social aggression in a double-blind, placebo-controlled experiment including 90 healthy male participants. To this end, we developed an innovative paradigm in which participants were provoked by a malfunctioning joystick restraining them from a promised reward. As measures for aggression throughout the task the joystick amplitude was recorded and anger was assessed via emotional self-ratings. Participants reacted to the provocation with a significant shift to more negative emotions and increased implicit aggressive behavior, reflected in the force exerted to pull the joystick following provocation. Importantly, the study demonstrated first evidence for a modulating influence of testosterone on non-social aggression in males: Self-rated anger was significantly elevated in the testosterone group compared to the placebo group as a function of provocation. Testosterone administration did not significantly influence the implicit aggressive response. These findings demonstrate a potentiating effect of testosterone on provocation-related anger in a non-social context. Furthermore, the results highlight the importance of disentangling different components of aggression and characterizing different influencing factors when inferring on hormonal effects.